Aplikasi Diagnosis Penyakit Thallasaemia Berbasis Android - Fadlillah, Nuzul Imam (APMMI - Asosiasi Profesi Multimedia Indonesia, 2020)
Abstract - Expert system for diagnosis of thallasaemia disease and its prevention is an expert system designed as a tool to diagnose and prevent thallasaemia disease with the knowledge base. Expert systems are an android based system that contains knowledge of one or more human experts on a specific field, with expert systems not necessarily replacing the role of experts but as a means of helping to know the diagnosis of the type of disease before consulting an expert. Expert system method used is naive bayes. This expert system will display a selection of symptoms that can be selected by the user, where each choice of symptoms brings the user to the next symptom choices to get the end result, the system will display a selection of user symptoms, and diseases suffered. The system provides results of the possibility of the disease experienced, the percentage of confidence, and the value of confidence given by the user in answering questions during the disease diagnosis session when using this system. Keywords: Expert system, Thallasaemia disease Abstrak - Sistem pakar untuk diagnosis penyakit thallasaemia dan cara pencegahannya ini merupakan suatu sistem pakar yang dirancang sebagai alat bantu untuk mendiagnosis dan mencegah penyakit thallasaemia dengan basis pengetahuan yang dinami. Sistem pakar merupakan sistem berbasis android yang mengandung pengetahuan dari satu atau lebih pakar manusia mengenai suatu bidang spesifik, dengan adanya sistem pakar bukan berarti akan menggantikan perannya para pakar melainkan sebagai sarana untuk membantu mengetahui diagnosis jenis penyakit sebelum berkonsultasi dengan ahlinya. Metode sistem pakar yang dipakai adalah naive bayes. Sistem pakar ini akan menampilkan pilihan gejala yang dapat dipilih oleh user, dimana setiap pilihan gejala membawa user kepada pilihan gejala selanjutnya sampai mendapatkan hasil akhir, sistem akan menampilkan pilihan gejala user, dan penyakit yang diderita. Sistem tersebut memberikan hasil berupa kemungkinan penyakit yang dialami, presentase keyakinan, serta nilai keyakinan yang diberikan oleh pengguna dalam menjawab pertanyaan selama sesi diagnosis penyakit ketika menggunakan sistem ini. Kata kunci: Sistem pakar, Penyakit Thallasaemia